2022
DOI: 10.1038/s41598-021-03978-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum optical immunoassay: upconversion nanoparticle-based neutralizing assay for COVID-19

Abstract: In a viral pandemic, a few important tests are required for successful containment of the virus and reduction in severity of the infection. Among those tests, a test for the neutralizing ability of an antibody is crucial for assessment of population immunity gained through vaccination, and to test therapeutic value of antibodies made to counter the infections. Here, we report a sensitive technique to detect the relative neutralizing strength of various antibodies against the SARS-CoV-2 virus. We used bright, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the study, neutralizing antibodies (IgG) containing sample showed no attachment of nanoparticles with ACE2 coated substrate while nanoparticles exhibited a strong affinity for binding with ACE2 coated substrates which lacks neutralizing antibodies. More importantly, developed SUPPV NPs possessed the highest sensitivity against SARS-CoV-2 with a detection limit of 4 ng/ml which was comparatively lower than the commercially available diagnostic kit with a detection limit of 19ng/ml [133] .…”
Section: Nanoparticle-based Diagnostic Approach Against Covid 19mentioning
confidence: 91%
“…In the study, neutralizing antibodies (IgG) containing sample showed no attachment of nanoparticles with ACE2 coated substrate while nanoparticles exhibited a strong affinity for binding with ACE2 coated substrates which lacks neutralizing antibodies. More importantly, developed SUPPV NPs possessed the highest sensitivity against SARS-CoV-2 with a detection limit of 4 ng/ml which was comparatively lower than the commercially available diagnostic kit with a detection limit of 19ng/ml [133] .…”
Section: Nanoparticle-based Diagnostic Approach Against Covid 19mentioning
confidence: 91%
“…To understand the ability of NAbs to block the binding of viruses to their receptors, many methods have been established to measure these antibodies, such as the plaque reduction neutralization test (PRNT), which is considered the gold standard; the highly sensitive pseudovirus neutralization assay; the simple enzyme-linked immunosorbent assay; and the lateral flow immunoassay, which can be used outside of the laboratory [ [35] , [36] , [37] , [38] ]. The research progress on technologies for the detection of NAbs against SARS-CoV-2 were reviewed in this paper by consulting the literature, with an aim to identify research directions and references for researchers and medical staff.…”
Section: Methods Of Neutralizing Antibody Detectionmentioning
confidence: 99%
“…More methods are used for neutralizing antibody detection for SARS-CoV-2, in addition to the above methods. A quantum optical tool is developed to measure the activity of NAbs, which using immunofluorescence technology and upconversion nanoparticles as fluorescent labels, and the sensitivity of this assay can reach 4.0 ng/ml [ 38 ]. Britto et al developed a rapid detection method called covariant scanning to detect the blocking interactions between the ACE2 receptor and the S protein of wild-type SARS-CoV-2 and three other variants [ 101 ].…”
Section: Methods Of Neutralizing Antibody Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosensors are an inseparable and important element for the progress and quality of human life [1]. These devices have various applications in the medical, chemical, pharmaceutical, food and health industries, including detecting environmental pollution, food quality, medicine, diseases, and are powerful tools for identifying biological molecules [2][3][4]. The biosensing technique, based on surface plasmon resonance (SPR), has attracted a lot of attention due to its advantages, including * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%